2017
DOI: 10.15557/cgo.2017.0001
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations of the Polish Gynecological Oncology Society for the diagnosis and treatment of ovarian cancer

Abstract: Due to the significant risk for ovarian cancer in carriers of BRCA1 and BRCA2 mutation, bilateral salpingo-oophorectomy is recommended after the patient has completed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 88 publications
0
34
0
1
Order By: Relevance
“…Even the slightest chance to avoid such radical surgery should be considered by experts and applied if possible, as in the case of this patient. Specialists in gynecology and oncology concluded that the best method in this case would be unilateral salpingo-oophorectomy with staging procedures [6,17]. In addition, adjuvant chemotherapy should be used after surgery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Even the slightest chance to avoid such radical surgery should be considered by experts and applied if possible, as in the case of this patient. Specialists in gynecology and oncology concluded that the best method in this case would be unilateral salpingo-oophorectomy with staging procedures [6,17]. In addition, adjuvant chemotherapy should be used after surgery.…”
Section: Discussionmentioning
confidence: 97%
“…It should be noted that, in the case of recurrent JGCT, total abdominal hysterectomy and bilateral salpingo-oophorectomy is the recommended method [16,17]. However, in the case of such a young patient, gynecologists should also take care of her reproductive health [1,9].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of ovarian cancer is a difficult process, which includes combined therapy . To implement the most appropriate treatment, it is necessary to establish grading (G1, G2 or G3) and the histological type of OC .…”
Section: Standard Treatmentmentioning
confidence: 99%
“…To implement the most appropriate treatment, it is necessary to establish grading (G1, G2 or G3) and the histological type of OC . Optimal debulking surgery is the strongest prognostic factor for the survival rate at all OC stages .…”
Section: Standard Treatmentmentioning
confidence: 99%
See 1 more Smart Citation